Is the wage curve formal or informal? Evidence for Colombia - Raúl Ramos; Juan C. Duque; Jordi Suri\~nach (Institute for the Study of Labor (IZA), 2009)
The objective of this paper is to analyse the existence or not of a wage curve in Colombia, paying special attention to the differences between formal and informal workers, an issue that has been systematically ignored in the wage curve literature. The obtained results using microdata from the Colombian Continuous Household Survey (CHS) between 2002 and 2006 show the existence of a wage curve with a negative slope for the Colombian economy. Using information on metropolitan areas, the estimates of the elasticity of individual wages to local unemployment rates was -0.07, a value that is very close to those obtained for other countries. However, the disaggregation of statistical information for formal and informal workers has shown significant differences among both groups of workers. In particular, for the less protected groups of the labour market, informal workers (both men and women), a high negatively sloped wage curve was found. This result is consistent with the conclusions from efficiency wage theoretical models and should be taken into account when analysing the functioning of regional labour markets in developing countries.
urn:nbn:de:101:1-200910141405
Keywords: J30; J60; O17; 330; Wage curve; unemployment; formal and informal sectors; Lohnkurve; Informeller Sektor; Privatwirtschaft; Schätzung; Kolumbien